Financial Literacy for Sheep Fattening Youth & Women’s Groups in Ethiopia - Wamatu, Jane; Ekule, Muluken (International Center for Agricultural Research in the Dry Areas, 2022)
A training report on financial literacy for Sheep Fattening Youth and Women Groups.